Buy it! : what's in it for your customers? - Magnacca, Mark, 1969- (FT Press Delivers elements., 2010)
"This Element is an excerpt from So what?: how to communicate what really matters to your audience (ISBN: 9780137158263) by Mark Magnacca. How to uncover and communicate the "So What?" benefits your customers really care about: the benefits that drive breakthrough success--in products, services, and in your own career!"--Resource description page.